Analisis Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK EMKM) pada Usaha Mikro Kecil dan Menengah (UMKM) di Kec. Kualuh Selatan Kab. Labuhanbatu Utara - Ainun, Sri; Harmain, Hendra; Tambunan, Khairina (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research is to analyze the application of accounting based on SAK EMKM to UMKM in South Kualuh Selatan, North Labuhanbatu Utara. This research was conducted using qualitative methods with a descriptive approach and the application of recording financial reports based on SAK EMKM with primary and secondary data taken from UMKM in South Kualuh Selatan, North Labuhanbatu Utara. Data collection techniques in this research used observation, interview and documentation techniques and the analysis techniques used were data reduction, presentation and drawing conclusions. The research results show that the majority of Micro, Small and Medium Enterprise Owners (UMKM) understand SAK EMKM. Information in financial reports is still presented very simply and manually. The difficulties faced by UMKM players are the lack of training courses on financial reports and SAK EMKM by practitioners, lack of time, they assume that financial reports are difficult to understand, and low awareness of improving financial reports in accordance with SAK EMKM. Keywords: SAK EMKM, Financial Report Recording System, UMKM